Fé e dinâmicas religiosas na América (luso) Latina. Da ambiguidade à busca de uma matriz comum - Oliveira, Pedro Rubens Ferreira de (Revista Eclesiástica Brasileira, 2019)
Os cristãos do Brasil, depois de mais de cinco séculos de evangelização, encontram-se às voltas com uma efervescência religiosa sem precedentes e uma ambiguidade sem limites. Três figuras contemporâneas explicitam a crise: as Comunidades Eclesiais de Base, a Renovação Carismática Católica e o Neopentecostalismo autônomo. Esse fenômeno religioso impressiona não tanto por uma simples perda de adeptos por parte do catolicismo, mas pela migração de fiéis de uma Igreja para outra, além dos conflitos entre esses grupos. Não se trata, a rigor, de “retorno do religioso”, mas de recomposição do cristianismo. No entanto, as manifestações plurais referem-se à mesma matriz: o catolicismo popular, memória viva da evangelização e do encontro da mensagem evangélica com as culturas que configuram a mestiçagem do povo brasileiro. Abstract: Brazilian Christians, after more than five centuries of evangelization, find themselves involved in a religious effervescence without precedents and in the midst of endless ambiguity. Three contemporary figures explain the crisis: the Ecclesial Grassroots Communities, the Charismatic Catholic Renewal and the Autonomous Neo-Pentecostalism. This religious phenomenon is striking not only because of a mere loss of followers on the part of Catholicism, but also in view of the faithful’s migration from one Church to another, besides the existing conflicts between these groups. Strictly speaking, the question is not a “return to religiosity” but the re-composition of Christianity. However, the plural manifestations refer to the same matrix: popular Catholicism, live memory of the evangelization and of the encounter of the evangelical message with the cultures that configure the miscegenation of the Brazilian people.